The Nuclear 35S rDNA World in Plant Systematics and Evolution: A Primer of Cautions and Common Misconceptions in Cytogenetic Studies - Rosselló, Josep A.; Maravilla, Alexis J.; Rosato, Marcela (Frontiers in Plant Science, 2022)
The ubiquitous presence of rRNA genes in nuclear, plastid, and mitochondrial genomes has provided an opportunity to use genomic markers to infer patterns of molecular and organismic evolution as well as to assess systematic issues throughout the tree of life. The number, size, location, and activity of the 35S rDNA cistrons in plant karyotypes have been used as conventional cytogenetic landmarks. Their scrutiny has been useful to infer patterns of chromosomal evolution and the data have been used as a proxy for assessing species discrimination, population differentiation and evolutionary relationships. The correct interpretation of rDNA markers in plant taxonomy and evolution is not free of drawbacks given the complexities derived from the lability of the genetic architecture, the diverse patterns of molecular change, and the fate and evolutionary dynamics of the rDNA units in hybrids and polyploid species. In addition, the terminology used by independent authors is somewhat vague, which often complicates comparisons. To date, no efforts have been reported addressing the potential problems and limitations involved in generating, utilizing, and interpreting the data from the 35S rDNA in cytogenetics. This review discusses the main technical and conceptual limitations of these rDNA markers obtained by cytological and karyological experimental work, in order to clarify biological and evolutionary inferences postulated in a systematic and phylogenetic context. Also, we provide clarification for some ambiguity and misconceptions in terminology usually found in published work that may help to improve the usage of the 35S ribosomal world in plant evolution.